Desclassification in knowledge organization: a post-epistemological essay - Gutiérrez, Antonio García (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2012)
The contents of the digital network stem from different forms, logics and cultures of knowledge. Once on the Net, however, they are all submitted to unifying formats and logics provided by digital technology itself. A technology is, first of all, the product of a given culture. Every culture and identity classifies and names all kinds of material and symbolic objects. Nowadays, the West is the one culture that has taken upon itself the task of global classification supported by its own digital networks. Classification is an epistemological tool provided by modern rationality whose internal structures and modes of inference are derived from metonymic, dichotomic and analogical reductions of the diversity of current worlds. In this paper, a kind of practical Hermeneutics, called “declassification”, is introduced and proposed as the route to a knowledge which overcomes organizational epistemology. Declassification is an open system that installs logical pluralism in the core of understanding and enunciation processes through meta-cognitive tools. Keywords: Classification. Digital network. Epistemology. Hermeneutics. Link para o texto completo (PDF) http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/article/view/475